Analisis Pengaruh Fasilitas dan Produk Terhadap Kepuasan Nasabah di PT BPR Saribumi Cabang Masaran - Trisnowati, Juni (Responsibilitas, 2011)
This research has the goal of 1. To determine the effect on customer satisfaction at the facilities of PT BPR Saribumi Cabang Masaran 2. To determine the effect of the product on customer satisfaction in PT BPR Saribumi Cabang Masaran. The hypothesis in this study are: 1. Allegedly there is a significant influence on customer satisfaction among facilities in PT BPR Saribumi Cabang Masaran 2. Allegedly there is a significant effect of the product on customer satisfaction in PT BPR Saribumi Cabang Masaran 3. Allegedly a significant difference between the facility and the product simultaneously on customer satisfaction in PT BPR Saribumi Cabang Masaran. The data required in this study is primary data that comes respondents, and secondary data such as company profiles, theories relating to the issues discussed in this study. Data collection methods used in this research is to spread questionnaires to the respondents, and through interviews of some employees, the secondary data obtained from company documents and books relating to the subject matter covered. The results of the data analysis in this study it can be concluded that: 1. There is a significant relationship between facility on customer satisfaction in PT BPR Saribumi Cabang Masaran 2. There is a significant effect of the product on customer satisfaction in PT BPR Saribumi Cabang Masaran 3. There is a significant relationship between facilities, and products simultaneously on customer satisfaction in PT BPR Saribumi Cabang Masaran. Keywords: Facilities, Products and Customer Satisfaction